Smoking Paradox in Stroke Survivors?: Uncovering the Truth by Interpreting 2 Sets of Data. Issue 4 (April 2020) - Wang, Hao-Kuang; Huang, Chih-Yuan; Sun, Yuan-Ting; Li, Jie-Yuan; Chen, Chih-Hung; Sun, Yu; Liu, Chung-Hsiang; Lin, Ching-Huang; Chang, Wei-Lun; Lee, Jiunn-Tay; Sung, Sheng-Feng; Yeh, Po-Yen; et al.
Abstract : Background and Purpose—: The observation that smokers with stroke could have better outcome than nonsmokers led to the term "smoking paradox." The controversy of such a complex claim has not been fully settled, even though different case mix was noted. Analyses were conducted on 2 independent data sets to evaluate and determine whether such a paradox truly exists. Methods—: Taiwan Stroke Registry with 88 925 stroke cases, and MJ cohort with 541 047 adults participating in a medical screening program with 1630 stroke deaths developed during 15 years of follow-up (1994–2008). Primary outcome for stroke registry was functional independence at 3 months by modified Rankin Scale score ⩽2, for individuals classified by National Institutes of Health Stroke Scale score at admission. For MJ cohort, mortality risk by smoking status or by stroke history was assessed by hazard ratio. Results—: A >11-year age difference in stroke incidence was found between smokers and nonsmokers, with a median age of 60.2 years for current smokers and 71.6 years for nonsmokers. For smokers, favorable outcome in mortality and in functional assessment in 3 months with modified Rankin Scale score ⩽2 stratified by the National Institutes of Health Stroke Scale score was present but disappeared when age and sex were matched. Smokers without stroke history had a ≈2-fold increase in stroke deaths (2.05 for ischemic stroke and 1.53 for hemorrhagic stroke) but smokers with stroke history, 7.83-fold increase, overshadowing smoking risk. Quitting smoking at earlier age reversed or improved outcome. Conclusions—: "The more you smoke, the earlier you stroke, and the longer sufferings you have to cope." Smokers had 2-fold mortality from stroke but endured stroke disability 11 years longer. Quitting early reduced or reversed the harms. Abstract : Supplemental Digital Content is available in the text.